Le Paléolithique moyen dans le nord du Sénonais (Yonne) Contexte géomorphologique, industries lithiques et chronostratigraphie - Deloze, Valérie; Depaepe, Pascal; Gouédo, Jean-Marc (Documents d'archéologie française, 1994)
Fine Middle Palaeolithic sites between Montereau (Seine-et-Marne) and Troyes (Aube) were excavated over large areas during the construction of the A5 motorway : these researches have allowed a renewed approach to this type of open-air deposit. the detailed analysis of the stratified lithic material and the pedo-seditnentary phases have supported the chronostratigraphical attributions : the successions of archaeological levels lie between 200 000 and 40 000 years B.C. The Micoquian industry is recognised at Vinneufl/Les Hauts Massous (Yonne) whilst the Mousterian industries carry on on the sites of the Vanne valley (Aube). This volume constitutes the first survey of the Middle Palaeolithic occupation of this part of the Paris basin, placed in its geological context.